2006
DOI: 10.1159/000096340
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Protein Profiling by Proteomic Analysis in Camptothecin-Resistant PC3 and Camptothecin-Sensitive LNCaP Human Prostate Cancer Cells

Abstract: Introduction: Drug resistance is a major obstacle for the therapy of prostate cancer, but its underlying mechanisms are not clarified. To detect some candidate marker proteins which may confer resistance to the anticancer drug camptothecin (CPT; DNA topoisomerase 1 inhibitor), the current study deals with the comparative proteomic profiling of CPT-resistant PC3 and CPT-sensitive LNCaP human prostate cancer cell lines which have been widely employed as a useful model to investigate prostate cancer cells. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Our proteomic analysis revealed a panel of proteins increased in a gemcitabine-resistant NSCLC cell line compared with its gemcitabine-sensitive control. Among the differently regulated proteins, six proteins (60 kDa heat shock protein, alpha enolase, heat shock cognate 71 kDa protein, protein disulfide isomerase, sorcin, annexin A1) have been found to be related to chemotherapy resistance in previous proteomic studies [13][14][15][16][17][18], and our findings are consistent with most of the previous works (details in Table 1). Furthermore, our study also identified eight gemcitabine-resistance-associated proteins which have not been reported in previous proteomic studies on chemotherapy resistance (details in Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…Our proteomic analysis revealed a panel of proteins increased in a gemcitabine-resistant NSCLC cell line compared with its gemcitabine-sensitive control. Among the differently regulated proteins, six proteins (60 kDa heat shock protein, alpha enolase, heat shock cognate 71 kDa protein, protein disulfide isomerase, sorcin, annexin A1) have been found to be related to chemotherapy resistance in previous proteomic studies [13][14][15][16][17][18], and our findings are consistent with most of the previous works (details in Table 1). Furthermore, our study also identified eight gemcitabine-resistance-associated proteins which have not been reported in previous proteomic studies on chemotherapy resistance (details in Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…These cell lines differ in their phenotypes and malignancy levels and reflect the androgenindependent progression of PCa: more interestingly, they show dissimilar expression profiles of ANXA1 protein. 16 Thus, we have analyzed the effects of shortand long-term hypoxic conditions on ANXA1 expression and on the metastatic-associated functional behaviors of transiently ANXA1 knock down and overexpression in PCa cells.…”
Section: Introductionmentioning
confidence: 99%
“…ANX1 exerts different effects in different cancers. Studies have indicated ANX1 was associated with the occurrence of prostate cancer (12) and pancreatic cancer (13). Paweletz et al (14) found that the loss or decreased expression of ANX1 was related to the early events in esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%